Effect of onion on blood lipid profile: A meta‐analysis of randomized controlled trials. Issue 7 (13th May 2021) - Huang, Wang; Tang, Gang; Zhang, Linyu; Tao, Jie; Wei, Zhengqiang
Abstract: Background: Studies indicate that onion supplementation may be effective in the treatment of dyslipidemia; however, the results remain controversial. This meta‐analysis was conducted to evaluate potential benefits of onion on lipid profile. Methods: Up to 12 October 2020, PubMed, Cochrane Library, Web of Science, and Scopus were searched for randomized controlled trials evaluating the effects of onion on lipid profile. Mean differences (MD) and 95% confidence intervals (CI) were calculated. Meta‐analysis was conducted using the fixed‐effects model. Results: Ten trials with 446 participants in total were included in the meta‐analysis. The pooled findings of 10 studies suggested that onion supplementation significantly improved high‐density lipoprotein cholesterol (HDL) (MD: 2.29 mg/dl; 95% CI: 0.87, 3.72; I 2 = 0%) and low‐density lipoprotein cholesterol (LDL) (MD: −6.64 mg/dl; 95% CI: −10.91, −2.36; I 2 = 32%), while onion supplementation did not significantly lower triglycerides (TG) (MD: −6.55 mg/dl; 95% CI: −15.64, 2.53; I 2 = 45%). Analysis of nine trials showed a significant reduction in total cholesterol (TC) (MD: −5.39 mg/dl; 95% CI: −10.68, −0.09; I 2 = 49%) in patients with onion supplementation compared to the control group. Conclusion: In summary, supplementation of onion was beneficial to control dyslipidemia, including improving levels of HDL, LDL, and TC, but could not reduce TG level. The therapeutic benefits of onion for dyslipidemia need to be treated with caution considering that some of the results are not robust. Abstract : Cardiovascular diseases are, currently, the leading cause of death globally, accounting for about one third of all deaths. Controlling blood lipids can effectively reduce the risk of cardiovascular diseases. Onion supplementation was beneficial for blood lipids, including improving plasma levels of HDL, LDL, and TC.